Detection of paint polishing defects. (21st May 2018) - Rebeggiani, S; Wagner, M; Mazal, J; Rosén, B-G; Dahlén, M
Abstract: Surface finish plays a major role on perceived product quality, and is the first thing a potential buyer sees. Today end-of-line repairs of the body of cars and trucks are inevitably to secure required surface quality. Defects that occur in the paint shop, like dust particles, are eliminated by manual sanding/polishing which lead to other types of defects when the last polishing step is not performed correctly or not fully completed. One of those defects is known as 'polishing roses' or holograms, which are incredibly hard to detect in artificial light but are clearly visible in sunlight. This paper will present the first tests with a measurement set-up newly developed to measure and analyse polishing roses. The results showed good correlations to human visual evaluations where repaired panels were estimated based on the defects' intensity, severity and viewing angle.